Integrating Thermal Actuation and Acidochromism in Schiff Base Molecular Crystals - Sayak Nag (21387016) (2025)
Crystalline materials capable of responding to multiple external stimuli have garnered considerable attention in recent years due to their promising potential for various applications in smart materials, sensing, and actuation. In this paper, we report the synthesis and characterization of two developed linker-based Schiff base molecular crystals, designated as 1 and 2, both of which exhibit two distinct reversible stimuli-responsive behaviors: (i) a thermal expansion–contraction response during repeated heating and cooling cycles and (ii) a reversible acidochromic color change upon sequential exposure to acidic and basic vapors. Importantly, these two reversible responses are governed by entirely distinct underlying processes. The thermal expansion–contraction behavior is driven by a martensitic phase transition, from a low-temperature phase to a high-temperature phase, which involves rapid and reversible lattice displacive rearrangements. In contrast, the acidochromic color change arises from a disruption in the electronic conjugation within the molecular framework, where the system undergoes a transformation from an A−π–D−π–A (acceptor−π–donor−π–acceptor) configuration to an A−π–A−π–A (acceptor−π–acceptor−π–acceptor) configuration upon protonation, manifested by a distinct shift in optical absorption properties. The unique combination of these two reversible phenomenathermal expansion-contraction and acidochromic responseswithin a single material system offers significant potential for advanced applications, particularly in the development of acid-sensitive sensors and thermally responsive microactuators.